Perilaku Seksual Beresiko Anak Buah Kapal (ABK) Kaitannya Dengan Upaya Pencegahan HIV dan AIDS dan Infeksi Menular Seksual - Suryono, Lucky Aris; Widjanarko, Bagoes; Suryoputro, Antono (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2011)
Ship workers have high risk of infected by HIV, because they work far from home and sex industry in harbor is known. This research was aimed to descript sexual behavior of ship crew. The amount of sample was 59 respondents from 150 populations, which took by accidental sampling technique. This is explanatory research and using cross sectional study. Questioner is used to interview the respondent. The result was analyzed by univariate, bivariate and multivariate analysis. The result shows 54,2% of 59 ship crew engaged in sexual risk behavior. By bivariate, this behavior related to knowledge, attitude, accessibility and acceptability of condom and health services, and peer behavior. In multivariate, sexual risk behavior influenced by knowledge, attitude, lack of peer behavior, and accessibility and acceptability of condom.